Allelopathic potential of 73 weed species in Pakistan - Khan, Sadiqullah (2019)
This study represents the comprehensive screening of allelopathic activity of weeds in Pakistan by applying sandwich and dish pack methods. The source for existing research of weed control towards classifying the potent organic compounds for controlling weeds in crops is the screening of large quantities of plants. Strong allelopathic weeds species have been acknowledged from analysis to provide direction for further research. Under laboratory conditions 73 weeds species were examined for their allelopathic potentials through latest bioassay activity evaluation techniques. The research information generated from the present work can be used as a benchmark for future research on the allelochemical identification and characterization. During the follow up work of present endeavor; methanolic leaf extracts of strongest allelopathic species shall be tested for antioxidant activities on crops pathogens and will also be recommended as allelopathic cover crop for biological control of weeds to support agro-environment conservation. In Pakistan, the allelopathic activity evaluation of plants through bioassay techniques is quite rare. There is a dire need to develop a complete data base of plants having strong allelopathic potential through application of these latest techniques.